Rhinobasis-Rekonstruktion durch "Galea-Periost-Calvarian-Split-Sandwich (GAP-CAS) -Technik" - Hoffmann, T. K.; Sandalcioglu, I. E. (Laryngo-Rhino-Otologie, 2011)
The frontal skull base represents an important barrier between the intracranial structures and the nasal sinuses preventing rhinoliquorrhea, ascending infections and brain prolaps.We reconstructed complete frontal skull base defects after interdisziplinary oncosurgery using a "Galea Periost – Calvaria Split – Sandwich (GAP-CAS) technique" with one half of the galea frontalis myofasccial flap torn to the nasal cavity, in-between the bone graft with the other half of the galea flap on top. By this technique it was possible to sufficiently cover the frontal skull base preventing cerebrospinal fluid leakage, meningitis and brain prolaps.